Epistemology and politics of interdisciplinary methodology - Rodríguez Zoya, Leonardo Gabriel (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2014)
The goal of this article is to propound a complex concept of interdiscipline, one that should be epistemologically rigorous, methodologically viable and politically critical. This implies to assume an explicit ideological position that involves a particular conception of the relation between science and society: interdisciplinary knowledge is necessary for a politics being able to intervene in complex problems affecting people life in Latin America.